Curcumin improves glucose tolerance via stimulation of glucagon‐like peptide‐1 secretion. Issue 3 (19th December 2016) - Kato, Masaki; Nishikawa, Sho; Ikehata, Akiho; Dochi, Kojiro; Tani, Tsubasa; Takahashi, Tsukasa; Imaizumi, Atsushi; Tsuda, Takanori
Abstract : GLP‐1 stimulates glucose‐dependent insulin secretion, and is an important factor in the treatment and prevention of type 2 diabetes. It is demonstrated that oral administration of curcumin significantly increases the plasma concentrations of GLP‐1 and insulin, resulting in the amelioration of impaired glucose tolerance in rats, and also curcumin‐induced GLP‐1 secretion is mediated via GPR 40/120 pathway. Abstract : Scope: Glucagon‐like peptide‐1 (GLP‐1) is a type of incretin secreted from enteroendocrine L‐cells. Our previous studies demonstrated that curcumin (a yellow pigment of turmeric) significantly increases the secretion of GLP‐1 in enteroendocrine L cell line (GLUTag cells). However, it is not clear whether its action in vivo directly enhances GLP‐1 secretion, which then leads to a reduction in blood glucose levels via the stimulation of insulin secretion. In addition, the molecular target of curcumin‐induced GLP‐1 secretion has not been clarified. Methods and results: Glucose tolerance was significantly improved in rats after pre‐administered curcumin (1.5 mg/kg) followed by intraperitoneal glucose injections via the stimulation of GLP‐1 secretion and the induction of insulin secretion. In GLUTag cells, curcumin‐induced GLP‐1 secretion was associated with G protein‐coupled receptor (GPR) 40/120. Furthermore, the glucose‐lowering effect induced by curcumin was significantly reduced after the administration of a GPR40/120 antagonist in rats. Conclusion: These findings demonstrate the biological function of curcumin as a GLP‐1 secretagogue and the possible molecular target that mediates GLP‐1 secretion. Increases in the secretion of endogenous GLP‐1 induced by curcumin may allow the dosages of other diabetic medicines to be reduced and aid in the prevention of diabetes.